2015
DOI: 10.1080/15377938.2014.984044
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ethnicity, Immigration Status, and Socioeconomic Status on Juror Decision Making

Abstract: The purpose of this research was to examine how ethnicity, immigration status, and socioeconomic status (SES) may contribute to juror bias. A total of 320 Euro-American venire persons were assigned to 1 of 8 criminal court trial transcript conditions that varied defendant ethnicity (Mexican or Canadian), immigrant status (undocumented or documented), and SES (low or high). Dependent measures were verdict, sentencing, culpability, and trait attributions. Results indicated that the low-SES undocumented Mexican d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Further, mock jury trial research has found that Indigenous Canadian defendants receive the harshest sentencing; this is likely attributable to implicit bias, particularly given that sentence length recommendation has been suggested to be a good measure of aversive racism as it is a continuous variable, subjective, and more sensitive than a standard dichotomous jury verdict of guilty or not guilty (Maeder et al, 2014). In another study, a panel of prospective jurors found low-SES undocumented Mexican defendants to be more culpable, more likely to receive a guilty verdict, and less likely to be granted parole compared with low-SES undocumented White Canadian defendants, despite no differences based on ethnic immigrant status in ratings of the defendants on a cold/warmth scale and competence traits assessment (Espinoza et al, 2015). The behavior of the jurors in making racially biased decisions and then denying having any racial biases (by way of the cold/warmth scale and competence traits assessment) suggests aversive racism.…”
Section: Different Types Of Individual Racismmentioning
confidence: 99%
“…Further, mock jury trial research has found that Indigenous Canadian defendants receive the harshest sentencing; this is likely attributable to implicit bias, particularly given that sentence length recommendation has been suggested to be a good measure of aversive racism as it is a continuous variable, subjective, and more sensitive than a standard dichotomous jury verdict of guilty or not guilty (Maeder et al, 2014). In another study, a panel of prospective jurors found low-SES undocumented Mexican defendants to be more culpable, more likely to receive a guilty verdict, and less likely to be granted parole compared with low-SES undocumented White Canadian defendants, despite no differences based on ethnic immigrant status in ratings of the defendants on a cold/warmth scale and competence traits assessment (Espinoza et al, 2015). The behavior of the jurors in making racially biased decisions and then denying having any racial biases (by way of the cold/warmth scale and competence traits assessment) suggests aversive racism.…”
Section: Different Types Of Individual Racismmentioning
confidence: 99%
“…To our knowledge, only two previous studies have examined public views on the criminal punishment of nonimmigration offenses committed by undocumented immigrants (Espinoza, Willis-Esqueda, Toscano, & Coons, 2015; Minero & Espinoza, 2016). Espinoza, Willis-Esqueda, Toscano, and Coons (2015) conducted a study using European American venire jurors ( n = 320) using a mock case involving a murder trial with a male defendant.…”
Section: Research On Public Views Of the Punishment Of Undocumented Offendersmentioning
confidence: 99%
“…To our knowledge, only two previous studies have examined public views on the criminal punishment of nonimmigration offenses committed by undocumented immigrants (Espinoza, Willis-Esqueda, Toscano, & Coons, 2015; Minero & Espinoza, 2016). Espinoza, Willis-Esqueda, Toscano, and Coons (2015) conducted a study using European American venire jurors ( n = 320) using a mock case involving a murder trial with a male defendant. Participants were assigned to one of the eight cases, which varied the defendant’s country of origin (Mexico or Canada), immigration status (undocumented or documented), and socioeconomic status (low or high).…”
Section: Research On Public Views Of the Punishment Of Undocumented Offendersmentioning
confidence: 99%
“…Approximately 13 per cent of the American population are African-American, yet in 2017, they accounted for 37.7 per cent of those incarcerated (Federal Bureau of Prisons, 2017). African-American males are 6.5 times more likely to be incarcerated than White males, with recent estimates suggesting that for African-American males in their 30s, one in ten is in prison or jail on any given day (Espinoza et al, 2015;The Sentencing Project, 2017). In 12 states, over half of the prison population is African-American; this percentage is highest in Maryland at 72 per cent.…”
Section: Minority Over-representationmentioning
confidence: 99%